Spreading the good apples out: Market entry dynamics of quality differentiated products - Esteban Jaimovich; Boryana Madzharova; Vincenzo Merella (Prague University of Economics and Business, Faculty of International Relations (FIR), 2024)
This paper examines firms' market entry strategies for quality differentiated goods, focusing on both initial and subsequent product-level entry decisions. Using a theoretical framework incorporating nonhomothetic preferences, we show that premium products are more likely to enter wealthier markets earlier, where producers can capture higher mark-ups. Furthermore, the determinants of follow-up market selection differ by product quality: for premium products, income plays a dominant role in shaping expansion paths, whereas geographic proximity remains the primary driver for low-quality products. Empirically, we test these predictions using micro-level data from the refrigeration industry. Our results confirm a strong positive relationship between market order of entry and income, with this effect being particularly pronounced for high-quality products. Additionally, we observe that, as product quality increases, follow-up markets tend to be geographically more dispersed relative to earlier markets.
Keywords: F1; F14; F23; L68; 330; Market entry; Gravity; Nonhomothetic preferences; Quality-differentiated products